Early Deterioration of the Right Ventricular Pacing Threshold Predicts the Increase in His‐Bundle Pacing Threshold During the Chronic Phase: A Single‐Center Retrospective Study - Kenji Baba; Shogo Sakamoto; Moritoshi Irishio; Tomotaka Yoshiyama; Yusuke Hayashi; Toru Kataoka; Daiju Fukuda (Journal of Arrhythmia)
ABSTRACT Background His‐bundle pacing (HBP) facilitates physiological ventricular activation. However, concerns about long‐term threshold deterioration persist. The predictors of chronic threshold elevation are not yet well established. Methods Between February 2018 and December 2021, HBP was attempted in 95 patients undergoing pacemaker implantation. Strict success criteria (threshold ≤ 2.0 V/0.4 ms) were applied, and 47 patients with successful HBP were monitored for over 3 years. We assessed pacing thresholds for both the His‐bundle and right ventricle (RV) at implantation, 1 week, 1 month, and annually thereafter. Lead shape was evaluated using chest radiography. Patients were categorized into two groups based on their His‐bundle pacing threshold: stable (≤ 3.5 V/0.4 ms) and deteriorated (> 3.5 V/0.4 ms). Results Deterioration in His‐bundle pacing thresholds was associated with increased RV pacing thresholds. Deterioration in RV pacing occurred earlier, with significant differences observed at 1 week post‐implantation (median RV: 1.87 vs. 3.25 V/0.4 ms, p = 0.032; His‐bundle: 1.0 vs. 1.25 V/0.4 ms, p = 0.212). Multivariate analysis identified an RV threshold ≥ 3.0 V/0.4 ms at 1 week (OR 10.7, p = 0.036) and lead bending on chest radiography (OR 12.8, p = 0.018) as independent predictors of chronic His‐bundle pacing threshold deterioration. Conclusion An elevated RV pacing threshold at 1 week post‐implantation and lead flexion at implantation may serve as early indicators of long‐term deterioration in His‐bundle pacing thresholds. When the RV pacing threshold increase is detected, it is important to closely monitor the patient and frequently adjust the output settings to prevent pacing failure.